PERGUMULAN KEBERAGAMAAN DI DUNIA BARAT - Baharudin, M (TEOLOGIA, 2014)
Abstract: This paper aims to find the answer to a fundamental question: what is religion? How is the phenomenon of religion in the western world? And how religious the Western world in this contemporary Era? In the discussion note several things, among others: 1). Religion is a system of beliefs and practices of life according to these beliefs. Religion is the rules on how to live a physically and mentally. Religionisa reference of life in its various aspects, including aspects of common life or social life. 2). In medieval times, religion is seen as having an absolute and universal truth concretely been visualized in the Western world. 3). In the postmodern era of modernity and religion is criticized and in distortion, the era of religion merely a matter of discussion and separated with practical life, religion is also considered to hinder the progression of man. Abstrak: Tulisan ini bertujuan menemukan jawaban mendasar atas pertanyaan: apa ituÂ  agama? Bagaimana fenomena agama di dunia Barat?Dan bagaimana keberÂagamaan dunia Barat pada Era kontemporel ini? Dalam pembahasan diketahui beberapa hal antara lain: 1). Agama ialah sistem kepercayaan dan praktek hidup yang sesuai dengan kepercayaan tersebut. Agama ialah peraturan tentang cara hidup lahir batin. Agama adalah acuan hidup berbagai aspeknya, termasuk aspek kehidupan bersama atau kehidupan sosial. 2). Pada abad pertengahan, agama dipandang sebagai yang memiliki kebenaran mutlak dan universal yang secara kongkrit pernah divisualisasikan di dunia Barat. 3). Pada era modernitas dan postÂmodern agama dikritik dan di distorsi, pada zaman tersebut agama sekedar menjadi bahan diskusi dan dipisahkan dengan kehidupan praktis, agama juga dianggap menghalangi progresivitas manusia. Keywords: Pergumulan, Keberagamaan, Dunia Barat